2005
DOI: 10.1016/j.bbr.2005.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Mentally represented motor actions in normal agingI. Age effects on the temporal features of overt and covert execution of actions

Abstract: The present study examines the temporal features of overt and covert actions as a function of normal aging. In the first experiment, we tested three motor tasks (walking, sit-stand-sit, arm pointing) that did not imply any particular spatiotemporal constraints, and we compared the duration of their overt and covert execution in three different groups of age (mean ages: 22.5, 66.2 and 73.4 years). We found that the ability of generating motor images did not differentiate elderly subjects from young subjects. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
70
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 53 publications
(92 reference statements)
13
70
0
1
Order By: Relevance
“…Personnier et al 2008;Skoura et al 2005). However, the absence of end-point differences in goaldirected aiming movements to visual target (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Personnier et al 2008;Skoura et al 2005). However, the absence of end-point differences in goaldirected aiming movements to visual target (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, although it was against an increased cognitive cost and additional neural resources, previous studies showed that older adults were able to reach levels of proprioceptive control of movement comparable to those of young adults (Batavia et al 1999;Boisgontier et al 2012;Deshpande et al 2003;Goble et al 2012a, b;Heuninckx et al 2008;Marks 1996;Pickard et al 2003). However, on the basis of the differences observed in motor imagery (Personnier et al 2010(Personnier et al , 2008Skoura et al 2005) and kinematic studies (Elliott and Hansen 2010;Goggin and Meeuwsen 1992;ReyRobert et al 2012; Seidler-Dobrin and Stelmach 1998), we hypothesised that (2) older adults were not able to reach the same level of end-point performance as the young adults in the fast speed condition due to the temporal constraints, making it impossible to use additional sub-movements to compensate for the presumably altered internal models. We also hypothesised that (3) older adults required a greater number of corrective sub-movements reflecting an intermittent control movement used to compensate for a presumed alteration of the internal models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The older adults had lower scores than those of the younger individuals in the first analysis and a significantly greater decline in task performance after 48h, suggesting that the older adults did not manage to preserve a functional motor skill as well as the young adults did (TUNNEY et al, 2004). According to the literature the findings cited may be related to problems of inhibitory control of a competing motor memory or to some aspects of action representation such as the intention to move or motor predictions (BROSSEAU; POTVIN; ROULEAU, 2007), which also become progressively fragile with age (SKOURA et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In action production, increasing age is accompanied by less precise motor planning (Reuter et al, 2015), less interhemispheric inhibition (Talelli, Waddingham, Ewas, Rothwell, & Ward, 2008), and reduced sensorimotor control of actions (Seidler & Stelmach, 1995). With respect to action perception, the accuracy of action prediction (Diersch, Cross, Stadler, SchĂŒtz-Bosbach, & Rieger, 2012), imagination (Personnier, Kubicki, Laroche, & Papaxanthis, 2010;Personnier, Paizis, Ballay, & Papaxanthis, 2008;Saimpont, Mourey, Manckoundia, Pfitzenmeyer, & Pozzo, 2010;Skoura, Papaxanthis, Vinter, & Pozzo, 2005), and the perception of the personal action range (Gabbard, Caçola, & Cordova, 2011) decreases from younger to older adults.…”
mentioning
confidence: 99%